The Influence Of Price Perceptions, Promotion And Halal Labeling On Instant Noodle Purchasing Decisions (Empirical Study on Sedaap Noodle Consumers in East Jakarta) - Herry Sussanto; Syaddad Rahman Sanusi (Asosiasi Dosen Muda Indonesia, 2025)
The era of globalization makes the development of the world and business for something faster, more efficient and practical. Especially in the food business, companies are competing to create practical and instant products, one example that can be taken is practical food such as instant noodles, the purpose of this study was to determine the effect of price perceptions, promotions, and halal labeling on purchasing decisions for Sedaap noodles. The number of samples taken in this study were 100 respondents. The process of distributing questionnaires to respondents was carried out online. This research method is quantitative and the technique used is non probability sampling technique. This study uses validity and reliability data tests. This research uses Smart PLS data analysis. The analysis obtained is that price perceptions and halal labeling have a positive and significant effect on purchasing decisions for Sedaap noodles in the East Jakarta area, while the promotion variable has no effect on purchasing decisions for Sedaap noodles in the East Jakarta area. And the halal labeling variable is the most dominant variable on purchasing decisions compared to other variables.